Endovascular administration of magnetized nanocarriers targeting brain delivery after stroke. Issue 2 (February 2022) - Grayston, Alba; Zhang, Yajie; Garcia-Gabilondo, Miguel; Arrúe, Mercedes; Martin, Abraham; Kopcansky, Peter; Timko, Milan; Kovac, Jozef; Strbak, Oliver; Castellote, Laura; Belloli, Sara; Moresco, Rosa M; et al.
The increasing use of mechanical thrombectomy in stroke management has opened the window to local intraarterial brain delivery of therapeutic agents. In this context, the use of nanomedicine could further improve the delivery of new treatments for specific brain targeting, tracking and guidance. In this study we take advantage of this new endovascular approach to deliver biocompatible poly(D-L-lactic-co-glycolic acid) (PLGA) nanocapsules functionalized with superparamagnetic iron oxide nanoparticles and Cy7.5 for magnetic targeting, magnetic resonance and fluorescent molecular imaging. A complete biodistribution study in naïve (n = 59) and ischemic (n = 51) mice receiving intravenous or intraarterial nanocapsules, with two different magnet devices and imaged from 30 min to 48 h, showed an extraordinary advantage of the intraarterial route for brain delivery with a specific improvement in cortical targeting when using a magnetic device in both control and ischemic conditions. Safety was evaluated in ischemic mice (n = 69) showing no signs of systemic toxicity nor increasing mortality, infarct lesions or hemorrhages. In conclusion, the challenging brain delivery of therapeutic nanomaterials could be efficiently and safely overcome with a controlled endovascular administration and magnetic targeting, which could be considered in the context of endovascular interventions for the delivery of multiple treatments for stroke.